Komodifikasi Wilayah Pasca Perang: Okinawa Sebagai Destinasi Wisata Tropis â€œBukan Jepang?â€ - Mukhlis Arifin; Kurniawaty Iskandar (LPPM Universitas Terbuka, 2022)
This paper will review the commodification of tourism in Okinawa in the form of dark tourism and how the form of Japanese identity formation in Okinawa is basically